Does speech rate influence intertemporal decisions? An experimental investigation - Chen, Josie I. (2022)
This paper experimentally examines the effect of speech rate on intertemporal decisions. In a delay-discounting task, subjects made a series of intertemporal choices between smaller-sooner and larger-delayed rewards and were asked to listen to a voice recording verbalizing the information for payoff options. We manipulated the speech rate of the voice recordings and administered two treatment conditions: Slow and Fast. We did not find an overall treatment effect in the acoustic manipulation.